The Spectrum of Fundus Autofluorescence Findings in Birdshot Chorioretinopathy - GianPaolo Giuliari; David M. Hinkle; C. Stephen Foster (Journal of Ophthalmology)
Objective. To describe the diverse patterns observed with the use of autofluorescence fundus photography (FAF) in patients with Birdshot chorioretinopathy (BSCR). Methods. A chart review of patients with BSCR seen at the Massachusetts Eye Research and Surgery Institution, who had autofluorescence fundus photography. The data obtained included age, gender, presence of the HLA-A29 haplotype, and current treatment. Results. Eighteen eyes with HLA-A29 associated BSCR were included. Four eyes presented with active inflammation. Correspondence of the lesions noted in the colour fundus photograph was observed in 3 eyes which were more easily identified with the FAF. Fifteen eyes had fundus lesions more numerous and evident in the FAF than in the colour fundus photograph. Conclusion. Because FAF testing provides valuable insight into the metabolic state of the PR/RPE-complex, it may serve as a useful noninvasive assessment tool in patients with posterior uveitis in which the outer retina-RPE-choriocapillaries-complex is involved.